2017
DOI: 10.1002/elps.201700213
|View full text |Cite
|
Sign up to set email alerts
|

Fast separation of enantiomers by capillary electrophoresis using a combination of two capillaries with different internal diameters

Abstract: The combination of capillaries with different internal diameters was used to accelerate the separation of enantiomers in capillary electrophoresis. Separation of R,S-1,1'-binaphthalene-2,2'-diyl hydrogen phosphate using isopropyl derivative of cyclofructan 6 was studied as a model system. The best separation conditions included 500 mM sodium borate pH 9.5 with 60 mM concentration of the chiral selector. Separation lasted approx. 1.5 min using the combination of 50 and 100 μm id capillaries of 9.7 cm and 22.9 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…The composition and pH of electrophoretic buffer are key factors that affect the separation of analytes in the CE, the peak intensity in the LIF detection, as well as the electric current stability of the equipment [46]. In our preliminary study, we observed significantly stronger peak intensity and better resolution of aflatoxins in alkaline buffers than in acidic buffers.…”
Section: Methods Optimizationmentioning
confidence: 62%
See 1 more Smart Citation
“…The composition and pH of electrophoretic buffer are key factors that affect the separation of analytes in the CE, the peak intensity in the LIF detection, as well as the electric current stability of the equipment [46]. In our preliminary study, we observed significantly stronger peak intensity and better resolution of aflatoxins in alkaline buffers than in acidic buffers.…”
Section: Methods Optimizationmentioning
confidence: 62%
“…In our preliminary study, we observed significantly stronger peak intensity and better resolution of aflatoxins in alkaline buffers than in acidic buffers. In addition, earlier studies show that the combination of Na 2 B 4 O 7 and Na 2 HPO 4 in the buffer solution produced excellent stability of electric current in CE separation . Therefore, Na 2 B 4 O 7 and Na 2 HPO 4 were chosen to prepare the background buffer, and the effect of their concentrations on aflatoxin separation and detection was examined under the optimal concentration of NaDC.…”
Section: Resultsmentioning
confidence: 99%
“…There are many applications in which the fusion of a capillary with small id against a large id is very advantageous, for instance, to increase detection sensitivity in CE [10], to decrease the run time in CE [5][6][7], to fabricate electrophoretic-hydrodynamic concentrators [4], and other niches of applications. Figure 2E-J shows such examples produced by the microfurnace technique.…”
Section: Fusion Splicing Of Thick Capillaries (Fsd > 150 μM)mentioning
confidence: 99%
“…Usually, polymer-made screw connectors and even epoxy glues are used to create connections in chromatographic columns, microfluidic devices [3], cell sorters, new set-ups in CE [4], and microchip electrophoresis. The advantages of connecting capillaries with different internal diameters were also demonstrated [5][6][7][8]. The advantage of using windows made of square capillaries [9] and enlarged cylindrical capillaries to increase detection limits was also demonstrated [10].…”
Section: Introductionmentioning
confidence: 97%
“…These approaches were not suitable for our application because we intended to have a continuous CE separation without decoupling from the high voltage field and a straightforward combination of conventional capillaries. There are other cases where capillaries with different IDs were coupled to achieve fast electrophoretic separations [14][15][16]. However, in these studies, injection and detection were performed in capillary segments of identical ID.…”
Section: Introductionmentioning
confidence: 99%